Principles of the New Ecosystem Formation: Multicultural Space - Kharlanov A. S., Strygina S. V., Trubnikova N. V., Chursina K. A., Sitokhova T. E., Khachirov K. A., Kotilko V. V., Ermakov D. N., Vragova E. V., Murzakulov N. A., Yslamov M. M., Shpak A. S., Olivio A., Semeno A. A., Danilchenko S. L., Platonova I. I., Sudakov O. V., Sudakov D. V., Danilchenko S. L., Smirnova S. P. (Principles of the New Ecosystem Formation: Multicultural Space, 2022)
the relevance of the chapter topic is due to the fact that very little attention is paid to the sound culture of schoolchildren's speech when teaching in general educational institutions. Recent studies have shown a large percentage of first graders who have speech impairments, in particular oral, when they enter school. Speech disorders affect not only the child's communication skills and learning outcomes in the disciplines «Russian language» and «Literature». The cognitive sphere of a child is a world of close interconnections, where a violation or underdevelopment of one of the structures slows down or disrupts the development of another. Deviations in speech development impede the formation of verbal-logical thinking, operations of analysis, synthesis, generalization, and classification, which leads not only to difficulties in mastering the program material of individual disciplines, but also generally negatively affects the cognitive development of the child. We see the search for effective approaches to solving this problem in STEAM education, an ever-growing direction, implying an approach in which several subject areas are integrated into interdisciplinary project and research activities. Having studied the existing developments in the framework of special education, we see a real possibility and need to develop a methodological manual based on the STEAM approach in order to form the sound culture of schoolchildren's speech.
Keywords: младшие школьники; younger schoolchildren; звуковая культура речи; STEAM подход; интерактивный логопедический стол; sound culture of speech; STEAM approach; interactive speech therapy table